Identifying potential and talented athletes in Tarung Derajat: A psychological perspective test - Setiawan, Ipang; Kurniawan, Wahyu Ragil (Journal Sport Area, 2023)
Identifying talented athletes is crucial for coaching and developing athletic talent in sports. Psychology plays a significant role in influencing athletes’ performance therefore it deserves attention in the identification process. This study aimed to identify potential athletes with the best abilities according to Tarung Derajat’s characteristics through a psychological perspective test. The research employs a survey method with a descriptive quantitative analysis approach. The SPQ20 questionnaire was used as the data collection instrument. The results of the psychological test were converted into percentages to determine the athletes’ potential, ranging from very potential to not potential. The research sample consisted of athletes from the training unit in the Semarang City area. The categorization criteria were based on norms derived from the highest-achieving athletes at the national level in Central Java province, with Tarung Derajat being the highest level. The findings indicated the following percentages for the achievement components: 68% for achievement, 66% for competitiveness, 62.9% for managing pressure, 67.78% for self-efficacy, 63.73% for fear of failure control, 63.83% for stress management, 65.56% for emotion, 70.33% for empathy, 54.40% for power, and 67.73% for aggressiveness. Based on a psychological perspective, this research concludes that 50 athletes (64%) in the training unit demonstrate potential as talented athletes. It is important to note that this study was limited to Tarung Derajat athletes in Central Java Province. The research findings contribute to the Central Java Tarung Derajat Training Centre by facilitating the categorization of athletes’ talent based on psychological aspects. Further, researchwas recommended to explore talent and potential of athletes from other perspectives not covered in this study.